PEMANFAATAN MEDIA DIGITAL INTERAKTIF DALAM BERMAIN PERAN UNTUK MENINGKATKAN KEPERCAYAAN DIRI ANAK DI TK ARRAHMAN KELOMPOK B - Husnul Khotimah; Ahmad Afandi; Firman Ashadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem of this study is that there are still many kindergarten children in group B who have difficulties in fostering confidence. This research aims to increase the confidence of early childhood children through the use of interactive digital media in role-playing activities in Arrahman Kindergarten group B. The methodology of this research uses Classroom Action Research with the Kemmis and Mc Tagart models which consists of four stages in Classroom Action Research, namely Planning, Acting, Observing, and Reflecting. The subjects in this study were all 25 children of group B. The data collection methods used are observation and documentation. The results of the study show that there is an increase in children's confidence with the use of interactive digital media in role-playing. It is proven that there is an increase in the percentage of the first cycle, which is 68% to 92% in the second cycle. It was concluded that the use of interactive digital media increases confidence in children.